Aspectos político-legais da educação do campo - Parente, Cláudia da Mota Darós [UNESP] (My University, 2014)
The article describes political and legal aspects of Brazilian education, through the analysis of Brazilian Constitutions, its amendments and major educational laws and resolutions in force until 2012, highlighting those that make direct reference to rural education and country education. It intends to identify the time when the educational legislation has incorporated the term “country education”, one of the struggles of the Movement for a Country Education. The use of the term “country education” will occur only in the first decade of this century. Despite the difficulties in consolidating country education, clearly the incorporation of this issue in the draft of the new National Education Plan (2011/2020), under discussion in Brazilian Congress.

O artigo descreve aspectos político-legais da educação brasileira, por meio da análise das Constituições Brasileiras, de suas emendas e das principais leis e resoluções educacionais em vigor até 2012, destacando aquelas que fazem referência direta à educação rural e à educação do campo. Intenciona-se identificar o momento em que a legislação educacional passou a incorporar o termo “educação do campo”, uma das lutas do Movimento por uma Educação do Campo. O uso do termo “educação do campo” vai acontecer apenas na primeira década do século XXI. Apesar das dificuldades enfrentadas para a consolidação da educação do campo, é visível a incorporação da temática no projeto de lei do novo Plano Nacional de Educação (2011/2020), em discussão no Congresso Nacional.
Political and Legal Aspects of Country Education